Coulomb-explosion imaging of concurrent photodissociation dynamics - Burt, M; Boll, R; Lee, J; Amini, K; Köckert, H; Vallance, C; Gentleman, A; Mackenzie, S; Bari, S; Bomme, C; Düsterer, S; Erk, B; et al. (American Physical Society, 2017)
The dynamics following laser-induced molecular photodissociation of gas-phase CH2BrI at 271.6 nm were investigated by time-resolved Coulomb-explosion imaging using intense near-IR femtosecond laser pulses. The observed delay-dependent photofragment momenta reveal that CH2BrI undergoes C-I cleavage, depositing 65.6% of the available energy into internal product states, and that absorption of a second UV photon breaks the C-Br bond of CH2Br. Simulations confirm that this mechanism is consistent with previous data recorded at 248 nm, demonstrating the sensitivity of Coulomb-explosion imaging as a real-time probe of chemical dynamics.